Mutual checking system for assessing trainee skills of thoracic surgery. (October 2021) - Miura, Naoko; Matsubara, Taichi; Takamori, Shinkichi; Akamine, Takaki; Haratake, Naoki; Shikada, Yasunori; Yamaguchi, Masafumi; Okamoto, Tatsuro; Takenoyama, Mitsuhiro
Background: Video-assisted surgery helps surgeons learn surgical skills efficiently. The aim of this study was to evaluate the effect of mutual evaluation of trainees' surgical techniques using tabulated common evaluation criteria. Methods: We created a check sheet in which a standard pulmonary lobectomy procedure was divided into six parts and the checkpoints to note listed. Both the trainees and trainers used tabulated common evaluation criteria to evaluate lobectomies performed by the trainees. Results: From September 2019 to March 2020, 30 lobectomies were performed by three trainees. The trainee's evaluations of their own procedures were relatively high at first, then decreased, then gradually increased; however, the trainers' evaluations showed no such tendency. Conclusions: Mutual evaluation of surgery using tabulated common evaluation criteria enables trainees to review their own surgery objectively and receive evaluations by trainers, thus helping them to avoid the Dunning–Kruger effect and efficiently acquire basic surgical skills.